Learning Specific Motivators Influencing Career Choices of Higher-Level Students in Nepal (The Batuk, 2026)
The selection of a career is a crucial developmental task that determines students' educational pathways, employability, and socio-economic prospects. This study examines the determinants of Nepalese higher secondary students' career decision-making on the foundation of Social Cognitive Career Theory, Human Capital Theory, and Holland's Typology. A quantitative cross-sectional design was employed, and 470 students from Grade 11, 12 and Bachelors 1st year students in Lalitpur District were surveyed. This information was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that subject interest, perceived ease of subject, financial returns, and future career opportunities have considerable impact on the decision of the students. Although personal interest is an important intrinsic motivator, extrinsic factors such as job security and financial benefits have more dominant influences, reflecting the socio-economic context of Nepal. The study highlights the pressing need for systematic career guidance, equitable access to resources, and education-to-labor market policy coordination to facilitate informed decision-making and strengthen human capital development.